Diguanylate cyclase Dgc1 synthesizes c-di-GMP and modulates WL gum exopolysaccharide production in Sphingomonas sp. WG - Hui Li; Yanhui Jia; Hangxu Liu; Zaimei Zhang; Mengqi Chen; Huiyu Zheng; Mengqing Xu; Mengmeng Zang; Dong Wang; Yawei Sun; Hu Zhu; Jiqian Wang (Bioresource Technology, 2026)

Robust water matrix tolerance for selective photocatalytic detoxification and decarboxylation of D-Glu and D-MeAsp in microcystin-LR via nanoconfinement-mediated active site regulation - Chengzhuo Yu; Jin Xu; Silong Wang; Li Xiong; Fanglan Geng; Yarui Wang; Lixia Zhao; Yawei Wang (Chemical Engineering Journal, 2026)

The meteorological and anthropogenic drivers of O3 and PM2.5 pollution in China's Ningbo based on WRF-CMAQ-ISAM - YuZhan Xie; Tijian Wang; Pulong Chen; Kuanguang Zhu; Tao Niu; Rong Li; Mengmeng Li; Hao Wu; Yawei Qu; Xu Liu; Congwu Huang (Atmospheric Pollution Research, 2026)

Experimental investigation of oxygen-enriched combustion in conjunction with plasma ignition and plasma-assisted combustion to improve ammonia combustion - Chen Wu; Qifu Lin; Dianwu Wu; Chengzhou Liu; Shilong Zhong; Hansheng Feng; Longwei Chen; Zhenyang Li; Yiman Jiang; Guangnan Luo; Yawei Song; Weiye Chen; et al. (Fuel, 2026)

Constructing atomic-scale proton channels in polymeric carbon nitride via synergistic oxygen and carbon defects for efficient CO2 photoreduction - Ruirui Wang; Yiming Wang; Jinhang Liu; Huixiong Jiang; Ran Wang; Yang Wang; Shunhang Wei; Xiaoxiang Xu; Yawei Wang (Chemical Engineering Journal, 2026)

Dual-nitrogen coordination engineering enables porous carbon-confined Pt-FeN4 atomic interfaces for durable, low-Pt PEM fuel cells - Xiaoqian Xu; Nengneng Xu; Qin Cao; Yuheng Guo; Meng Li; Yuhao Liu; Yawei Li; Guicheng Liu; Woochul Yang; Jong Min Kim; Momo Safari; Jinli Qiao (Chemical Engineering Journal, 2026)

Multi-mode and encapsulated droplet-based electricity generator for environmental sensing and cathodic protection - Miaomiao Cui; Peiyu Wu; Ruiqi Fang; Wenbo Zhao; Yuankai Jin; Yawei Feng; Fuhui Wang; Zhipeng Zhang; Xiangyu Li; Dake Xu (Chemical Engineering Journal, 2026)

Enhanced net carbon dioxide sink in rice-duckweed system: Evidence from the diurnal flux variation - Weixuan Liu; Ning Gao; Yawei Li; Xiaoyin Liu; Xue Zhou; Yihao Peng; Lili Zhu; Jian Meng; Junzeng Xu (Agriculture, Ecosystems & Environment, 2026)

Notable impact of urban ventilation corridors on the transport of particle-bound ultrashort-chain perfluoroalkyl substances in the atmosphere - Anen He; Feifei Li; Juan Li; Fanghan Sun; Han Fang; Xu Sun; Yanli Guo; Hailin Wang; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2026)

A portable source-informed machine learning framework for predicting heavy metals in legacy smelting sites with strong spatial heterogeneity - Xu Cao; Yan Liang; Yawei Zhao; Tianhuan Chen; He Huang; Tian Xie (Journal of Hazardous Materials, 2026)

Functional Lactiplantibacillus plantarum MT213 screened from traditional sourdough and its promising in-situ preservation in steamed bread - Danya Tong; Yajuan Zhang; Tianyi Zhang; Zhixin Wang; Shijie Wang; Xueming Xu; Yawei Ning (International Journal of Food Microbiology, 2026)

Scale-dependent divergent response of soil respiration and its variation under grazing and reduced precipitation in a sandy Pinus sylvestris var. mongolica plantation - Zi Li; Xu Han; Hengming Zhang; Jiang Zhao; Xiang Li; Guochuang Zhang; Yawei Wei; Shengjin Qin (Journal of Soils and Sediments, 2026)

Nearshore bathymetry estimation from SAR imagery based on the adaptive window guided by local wave direction - Lijie Diao; Yongsheng Xu; Yawei Zhao; Haimei Mo; Yanlei Du; Xiaolan Qiu; Jinsong Chong (International Journal of Remote Sensing, 2026)

Investigating the impact of different abuse methods on the thermal runaway behavior of lithium batteries under high-rate charge and discharge conditions - Yajun Huang; Weifeng Xu; Xiongqi Shen; Yinquan Zhao; Yang Cao; Wei Bai; Junling Wang; Yawei Lu; Zhirong Wang (Process Safety and Environmental Protection, 2026)

LC-MS/MS analysis of polar pesticides in mango: enantiomers, docking, and retention mechanisms - Hao Yang; Yue Geng; Shu Lin; Yawei Xu; Lu Wang; Yi Peng; Yaping Xu; Xiaowei Liu; Zeying He (Food Chemistry, 2026)

Cover crops potentially enhance soil organic carbon sequestration to offset greenhouse gas emissions without yield penalty towards net-zero rice agriculture - Ruitao Lou; Yong Li; Zhenghan Li; Zhifeng Xu; Yu Tang; Xiangping Jin; Junzeng Xu; Yawei Li; Yong He; Qianjing Jiang (Agriculture, Ecosystems & Environment, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

BRICS cooperation and ecological sustainability: Unveiling the roles of energy transition, technological innovation, and globalization - Jialiang Wu; Xi Xu; Weihao Wang; Jikun Jiang; Yawei Xue; Ling Jiang (Gondwana Research, 2026)

Short-term effect of changing water regimes on the soil nematode community in rice-duckweed system under water-saving irrigation - Zeeshan Ahmed; Junzeng Xu; Weixuan Liu; Xiaoyin Liu; Yawei Li; Hang Guo; Shengyu Chen (European Journal of Soil Biology, 2026)

Excellent infrared radiation performance and significant energy-saving efficiency of LaAlO3 ceramics via Ca2+/Co2+ co-doping - Qinghu Wang; Yangxi Liu; Guoping Wei; Liang Huang; Xueqing Wang; Shaobai Sang; Yibiao Xu; Xiong Liang; Yawei Li; Jiangtao Li; Olena Volkova; Emad M.M. Ewais; et al. (Chemical Engineering Journal, 2026)

Landslide assessment research in the three gorges reservoir area: A review of methodological advances and future directions - Yuandong Huang; Chong Xu; Xiaoyi Shao; Xiangli He; Zikang Xiao; Xiwei Xu; Yawei Xie; Xuning Nie; Xin Li (Bulletin of Engineering Geology and the Environment, 2026)

Brine-filled MXene “Sandwich” system for synergistically enhanced electrochemical energy storage and solar desalination - Bowen Liu; Xuedong He; Yawei Yang; Yuyao Shen; Yihong Liu; Qi Zhao; Xinye Xu; Mo Zhou; Tianyi Wang; Wenxiu Que (Chemical Engineering Journal, 2026)

Cardiac targeted delivery of Maresin 1 nanomedicine rescues microvascular obstruction after myocardial infarction - Yawei Zhao; Jing Zhang; Xiaohan Fan; Yue Cai; Wenting Du; Ziyi Yu; Biao Xu; Xuan Sun (Chemical Engineering Journal, 2026)

Impact of salinity on nitrogen cycling and microbial community functional potential in groundwater of the Yellow river delta - Huan Wang; Chuanshun Zhi; Yufei Jiao; Dan Xu; Wenfeng Gao; Yawei Kou; Xiancang Wu; Jing Bai; Hui Mu; Houliang Lu; Xiaonong Hu (Applied Geochemistry, 2026)

Efficient removal of nitrogen, phosphorus and antibiotics in freshwater aquaculture wastewater using a novel hybrid aeration biological filter - Dongyu Xia; Weina Dou; Yawei Tian; Lei Zhang; Cai Wang; Yong Wang; Jingyi Zhang; Yutong Han; Yanyan Xiao; Xu Yang; Xiang Mei (Journal of Environmental Management, 2025)

A study on a correction method for channel wave energy consistency under geophone-bolt coupling - Guangzhong Ji; Lingyun Shi; Yawei Zhang; Shuai Xu; Keyue Liu (Acta Geophysica, 2025)

Removal of insoluble barium scales from reverse osmosis membranes by grafting molecular springs - Xin Wen; Yuyan Hai; Rui Ma; Xu Liang; Yawei Duan; Jingyun Chen; Hui Wei; Rihua Xiong (Desalination, 2025)

Study on the NO2 pollution and its connection with PM2.5 and O3 in Dazhou based on source apportionment - Xu Liu; Pulong Chen; Congwu Huang; Tijian Wang; Tao Niu; Mengmeng Li; Rong Li; Hao Wu; Yawei Qu (Atmospheric Pollution Research, 2025)

Population challenge, economy, energy decarbonization and information and communication technology: insights of ecological footprint and biocapacity in Belt and Road countries - Jialiang Wu; Xi Xu; Weihao Wang; Jikun Jiang; Yawei Xue; Ling Jiang; Zichuan Quan (Environment, Development and Sustainability, 2025)

Unraveling the health contributions of five key bioactives in virgin olive oil: A dose-based comparative review - Yunfei Huang; Wenqing He; Mengyao Zhao; David Julian McClements; Yawei Xu; Lu Li; Wanyi Dong; Xueqin Hu; Chunmei Li (Trends in Food Science & Technology, 2025)

A hybrid approach for optimizing soil greenhouse gas flux predictions: integrating machine learning outputs into hyperparameter-tuned regression trees - Mostafa RASTGOU; Shangkun LIU; Jin WANG; Yawei LI; Junzeng XU; Yong HE; Qianjing JIANG (Pedosphere, 2025)

Preparation of magnesia directly from brine Mg(OH)2 and its performance optimization: The role of ZrSiO4 additive - Chengqing Hu; Yibiao Xu; Yawei Li; Wen Yan (Journal of Environmental Chemical Engineering, 2025)

Flexible erythritol-based spatiotemporal phase change films with multiple energy responses for wearable thermal management - Huimin Yan; Yan Kou; Shihui Zhang; Hanqing Liu; Nan Yin; Yawei Xu; Quan Shi (Chemical Engineering Journal, 2025)

The impact of the COVID-19 epidemic on anthropogenic emissions in the Beijing-Tianjin-Hebei region of China based on 3DVar sectoral emission inversion - Congwu Huang; Tao Niu; Tijian Wang; Mengmeng Li; Rong Li; Chaoqun Ma; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu; Yuzhan Xie (Journal of Hazardous Materials, 2025)

Graphene/epoxy coating with radiation heat dissipation properties for spacecraft thermal management - Ning Li; Yibo Zhang; Yawei Xu; Jing Li (Chemical Engineering Journal, 2025)

Excellent lithium storage performance of SnOx/Ti3C2 with low Sn content by controlling the oxygen vacancy content - Tingting Xu; Yawei Li; Jinghan Zhang; Haixiang Huang; Bogu Liu; Xiaohong Chen; Hong Zeng; Ying Wu (Chemical Engineering Journal, 2025)

Quaternary ammonium COF-based proton exchange membranes for enhanced electrochemical hydrogen compression - Xiao Pang; Ziwen Liu; Shuting Xu; Kexin Lv; Benbing Shi; Xu Dong; Na Xing; Zhong Gao; Shiyi Zhu; Leilang Zhang; Zengguang Yao; Lijuan Cheng; et al. (Chemical Engineering Journal, 2025)

Experimental study on the failure mechanism of interbedded anti-dip rock slope induced by underground mining - Nanyun Wang; Zuliang Zhong; Yawei Xu; Xinrong Liu; Kaixin Zhu (Journal of Mountain Science, 2025)

The impact of indoor air quality on work performance in urban office spaces: A machine learning approach - Xinyi Huang; Xiaohong Zheng; Yawei Xu; Jiale Zhai; Dengyun Wang; Hua Qian (Building and Environment, 2025)

Influence of alternate wetting and drying and duckweed on zooplankton abundance in rice paddy ecosystem - Zeeshan Ahmed; Weixuan Liu; Junzeng Xu; Yawei Li; Zahid Majeed (Journal of Environmental Management, 2025)

Genome-wide association study reveals growth-related mutations and candidate genes at early growth stages in largemouth bass (Micropterus salmoides) - Xiao Ma; Dongcai Chen; Zhilin Jia; Yue Xu; Zhigang Qiao; Lei Wang; Hongxia Jiang; Miao Yu; Yongjing Li; Xiaotian Gao; Chunlong Zhao; Yawei Shen; et al. (Aquaculture, 2025)

Co-incorporation of C and S into zero-valent iron to enhance trichloroethylene dechlorination: Kinetics, electron efficiency, and dechlorination capacity - Xuan Zhang; Siyu Xu; Yawei Gu; Ling Zhang; Longquan Zhang; Fengxu Shang; Xinze Song; Zhen Wang; Xiaoguo Shi; Honglei Zhang; Runze Bi; Jinbo Chen (Journal of Environmental Chemical Engineering, 2025)

Mechanism investigation into static magnetic field effects on enhancing surfactin productivity by Bacillus subtilis - Yamei Jin; Sirui Chen; Qiyan Zhao; Na Yang; Yawei Ning; Xueming Xu (Food Bioscience, 2025)

Air oxidation behavior of wet-mechanochemically synthesized pyrite FeS2: Fenton performance regulated by Fe species, sulfur vacancy and crystal facet ratio - Zunqing Wen; Xiaoguo Shi; Huiying Sui; Minglu Zhang; Longquan Zhang; Yawei Gu; Qing Feng; Ke Ma; Na Zhang; Mingzhe Wang; Ruiyan Zhang; Chongqing Xu; et al. (Chemical Engineering Journal, 2025)

Stability analysis of karst anti dip rock slope induced by underground coal mining - A case study of Jiguanling landslide, China - Zuliang Zhong; Erwei Liang; Nanyun Wang; Yawei Xu (Journal of Mountain Science, 2025)

Atmospheric fronts detection and cold/warm type determination based on wind field retrieval from SAR imagery - Xianen Wei; Jinsong Chong; Yawei Zhao; Wenjia Zhao; Yongsheng Xu (International Journal of Remote Sensing, 2025)

Titanium-based hollow fiber membrane: Fabrication, optimization, and electrochemical filtration treatment performance - Xiaoqing Yan; Zonglin Pan; Xinyuan Zhou; Shuo Liu; Hang Yu; Ruisong Xu; Yawei Shi; Xinfei Fan; Tianjun Sun; Yongxin Song; Chengwen Song (Journal of Environmental Chemical Engineering, 2025)

Genome-wide association analysis study on host resistance against the Aeromonas veronii of largemouth bass Micropterus salmoides - Meng Zhang; Xiao Ma; Zerui Wang; Yuqing Han; Zhilin Jia; Dongcai Chen; Yue Xu; Zhigang Qiao; Xinyu Jiang; Lei Wang; Hongxia Jiang; Miao Yu; et al. (Fish & Shellfish Immunology, 2025)

Unveiling the impact of aging on environmental sustainability in China: New insights from the Fourier ARDL approach - Zichuan Quan; Xi Xu; Jikun Jiang; Weihao Wang; Yawei Xue; Ling Jiang (Journal of Environmental Management, 2025)

Ultrasensitive and high selectivity detection of fibrin using Y-shaped DNA-homing peptide doped probe on localized surface plasmon resonance platform - Yawei Chen; Yuanfu Zhang; Xue Zhao; Wenyu Xu; Shuhao Wang (Analytica Chimica Acta, 2025)

Duckweed (Lemna minor L.) as a natural-based solution completely offsets the increase in ammonia volatilization induced by soil drying and wetting cycles in irrigated paddies - Weixuan Liu; Junzeng Xu; Yawei Li; Xiaoyin Liu; Xue Zhou; Yihao Peng; Yixuan Jia; Jian Gao; Qianjing Jiang; Yong He (Science of The Total Environment, 2024)

Heat stress induces a three-phase thermoregulatory response in different hot and humid environments in rats - Lei Li; Jikuai Chen; Juelin Chen; Yawei Wang; Yankun Pei; Man Wang; Wenjun Chang; Jun Ma; Qing Song; Shuogui Xu (Science of The Total Environment, 2024)

3DVar sectoral emission inversion based on source apportionment and machine learning - Congwu Huang; Tao Niu; Tijian Wang; Chaoqun Ma; Mengmeng Li; Rong Li; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu (Environmental Pollution, 2024)

Versatile plant genome engineering using anti-CRISPR-Cas12a systems - Yao He; Shishi Liu; Long Chen; Dongkai Pu; Zhaohui Zhong; Tang Xu; Qiurong Ren; Chuan Dong; Yawei Wang; Danning Wang; Xuelian Zheng; Fengbiao Guo; et al. (Science China Life Sciences, 2024)

CRISPR-Cpf1 system and its applications in animal genome editing - Yawei Han; Zisen Jia; Keli Xu; Yangyang Li; Suxiang Lu; Lihong Guan (Molecular Genetics and Genomics, 2024)

Meta-analysis of GHG emissions stimulated by crop residue return in paddy fields: Strategies for mitigation - Qianying Wu; Ruitao Lou; Yong He; Yawei Li; Zhiming Qi; Junzeng Xu; Ji Liu; Mostafa Rastgou; Qianjing Jiang (Journal of Environmental Management, 2024)

Comprehensive characterization of the differences in metabolites, lipids, and volatile flavor compounds between Ningxiang and Berkshire pigs using multi-omics techniques - Qian Wang; Hu Gao; Yawei Fu; Yue Chen; Gang Song; Zhao Jin; Yuebo Zhang; Jie Yin; Yulong Yin; Kang Xu (Food Chemistry, 2024)

CoAl-Layered Double Hydroxide Catalytic Membrane for Activation of Peroxymonosulfate Towards Efficient Degradation of Organic Pollutants - Yawei Shi; Tongwen Zhang; Qian Chang; Zonglin Pan; Ruisong Xu; Ya Sun; Guanghui Ding (Water, Air, & Soil Pollution, 2024)

Orbital-paced Oceanic Anoxic Event 2 evolution and astrochronology in the Mentelle Basin (Australia) at southern high latitudes - Kang Xu; Yi Zhong; H. Tsikos; Hongjin Chen; Yawei Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Effects of inorganic sodium on the soot generation of coal particle: Insights with PLIF and DFT calculation - Yawei Song; Sheng Su; Zheng Zhao; Jingyan Wang; Kai Xu; Jun Xu; Long Jiang; Yi Wang; Song Hu; Jun Xiang (Fuel, 2024)

Thyroid disrupting effects and the developmental toxicity of hexafluoropropylene oxide oligomer acids in zebrafish during early development - Xiaohui Zhao; Xianghan Meng; Dan Yang; Shasha Dong; Jianhui Xu; Dezhi Chen; Yawei Shi; Ya Sun; Guanghui Ding (Chemosphere, 2024)

Enhanced treatment of pyridine wastewater by a hybrid membrane biofilm reactor: Simultaneous biodegradation of pyridine and removal of nitrogen - Jingyi Zhang; Yawei Tian; Zhan Wang; Mengmeng Yang; Yong Wang; Han Gao; Zimiao Zhang; Yutong Han; Yanyan Xiao; Xu Yang; Xuanwei Zhao; Yue Wu; et al. (Process Safety and Environmental Protection, 2024)

Investigating functional mechanisms in the Co-biodegradation of lignite and guar gum under the influence of salinity - Bing Li; Hongyu Guo; Ze Deng; Linyong Chen; Changjiang Ji; Xiaokai Xu; Yawei Zhang; Song Cheng; Zhenzhi Wang (Journal of Environmental Management, 2024)

Low-permittivity BaCuSi4O10-based dielectric Ceramics: An available solution to connect low temperature cofired ceramic technology and millimeter-wave communications - Wei Wang; Xin Wang; Jian Bao; Jiapei Jiang; Zhen Fang; Biaobing Jin; Zhongqi Shi; Moustafa Adel Darwish; Yawei Chen; Qixin Liang; Meirong Zhang; Diming Xu; et al. (Chemical Engineering Journal, 2024)

Enhanced Fenton performance of wet-mechanochemically synthesized FeS2/Biochar: The multiple synergistic effect derived from mutual element doping - Zunqing Wen; Xiaoguo Shi; Yawei Gu; Ke Ma; Xiaozhe Song; Ao He; Chen Wang; Nianbo Zhang; Huiying Sui; Chongqing Xu; Rong Xue (Chemical Engineering Journal, 2024)

Alternating wet and dry irrigation cycles enhance the nitrogen “cache” function of duckweed in a rice-duckweed system - Weixuan Liu; Junzeng Xu; Yawei Li; Xiaoyin Liu; Ning Gao; Zeeshan Ahmed; Yihao Peng; Hao Liang; Qianjing Jiang; Yong He (Agriculture, Ecosystems & Environment, 2024)

Efficient degradation of organic pollutants with sodium percarbonate by activation with CuFeS2 prepared from precursors of different valence states - Yawei Shi; Qian Chang; Tongwen Zhang; Zonglin Pan; Ruisong Xu; Ya Sun; Guanghui Ding (Journal of Environmental Chemical Engineering, 2024)

Associations of environmental cadmium exposure with kidney damage: Exploring mediating DNA methylation sites in Chinese adults - Yuan Wei; Xiaochen Wang; Qi Sun; Wanying Shi; Wenli Zhang; Xu Gao; Yawei Li; Ruiting Hao; Xiaojie Dong; Chen Chen; Kangning Cao; Weilong Jiang; et al. (Environmental Research, 2024)

Hydrothermal liquefaction of pig carcasses to biofuel: A techno-economic analysis - Youzhou Jiao; Chao Chang; Gaojie Xu; Chao He; Xinxin Liu; Gang Li; Yawei Wang; Xiaohui Pan; Guizhuan Xu; Qibin Li; Liang Liu (Process Safety and Environmental Protection, 2024)

Exquisite visualization of mitophagy and monitoring the increase of lysosomal micro-viscosity in mitophagy with an unusual pH-independent lysosomal rotor - Rui Yang; Wei He; Changxin Zhu; Xifeng Yang; Yawei Kuang; Tao Zhu; Jingyang Xu; Yuang Zhao; Tingwang Jiang; Yushen Liu; Mengmeng Wei (Analytica Chimica Acta, 2024)

Sustainability evaluation of urban large-scale infrastructure construction based on dynamic fuzzy cognitive map - Hongyu Chen; Shidong Cheng; Yawei Qin; Wen Xu; Yang Liu (Journal of Cleaner Production, 2024)

Criticality assessment of minerals associated with China's battery technologies - Yawei Huang; Peng Wang; Yao Wang; Heming Wang; Yue Zhang; Xiaozhu Xu; Chao Wang; Qiang Yue; Tao Du; Wei-Qiang Chen (Journal of Cleaner Production, 2024)

New insights into Co3O4-carbon nanotube membrane for enhanced water purification: Regulated peroxymonosulfate activation mechanism via nanoconfinement - Huanran Ma; Guoqing Feng; Xiao Zhang; Chengwen Song; Ruisong Xu; Yawei Shi; Pengcheng Wang; Zhouhang Xu; Guanlong Wang; Xinfei Fan; Zonglin Pan (Chemosphere, 2024)

Maximizing the carbon sink function of paddy systems in China with machine learning - Jin Wang; Qingguan Wu; Yong He; Yawei Li; Junzeng Xu; Qianjing Jiang (Science of The Total Environment, 2024)

New insights into micro-algal astaxanthin's effect on deoxynivalenol-induced spleen lymphocytes pyroptosis in Cyprinus carpio: Involving mitophagy and mtROS-NF-κB-dependent NLRP3 inflammasome - Lei Diao; Wenjie Liu; Yawei Xu; Bin Zhang; Lingnan Meng; Rui Yin; Huijie Chen (Fish & Shellfish Immunology, 2024)

Integrating Software FMEA and STPA to Develop a Bayesian Network-Based Software Risk Model for Autonomous Ships - Xue Yang; Yawei Zhu; Tao Zhou; Sheng Xu; Wenjun Zhang; Xiangyu Zhou; Xiangkun Meng (Journal of Marine Science and Engineering, 2023)
The autonomous shipping industry is increasingly focusing on enhancing the safety and reliability of software-based systems. Conducting a risk assessment is a requirement for demonstrating the safety equivalence of autonomous ships based on such systems to conventional vessels. Traditional risk assessment models, however, primarily focus on hardware failures, often overlooking potential software-related failures and functional inadequacies. This study proposes a framework integrating Software Failure Mode and Effects Analysis (FMEA), System–Theoretic Process Analysis (STPA), and Bayesian Network (BN) for risk identification of autonomous ship software systems. The results of a case study reveal that the framework sufficiently addresses the multifaceted nature of risks related to software in autonomous ships. Based on the findings of this study, we suggest the need for standardization of software architecture development in the autonomous ship industry and highlight the necessity for an enhanced understanding of AI-specific risks and the development of tailored risk assessment methodologies.

WITHDRAWN: Orbital-paced Oceanic Anoxic Event 2 evolution and astrochronology in the Mentelle Basin (Australia) at southern high latitudes - Kang Xu; Yi Zhong; H. Tsikos; Hongjin Chen; Yawei Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Experimental research on the venting characteristics of methane and coal dust two-phase system mixture explosions - Xingyan Cao; Rui Huang; Yawei Lu; Zhirong Wang; Longtao Fan; Yangqing Zhou; Jianjun Xu (Fuel, 2023)

Micro-algal astaxanthin ameliorates polystyrene microplastics-triggered necroptosis and inflammation by mediating mitochondrial Ca2+ homeostasis in carp’s head kidney lymphocytes (Cyprinus carpio L.) - Lei Diao; Meiqi Ding; Hongzhen Sun; Yawei Xu; Rui Yin; Huijie Chen (Fish & Shellfish Immunology, 2023)

Degradation of norfloxacin by sulfur-doped iron-cobalt oxides activated perodisulfate: Synergism between free radicals and singlet oxygen - Luwei Zhai; Fengchun Li; Yuhai He; Xia Chen; Xuan Zhang; Yawei Gu; Chongqing Xu; Guihuan Yan; Xiaojing Feng; Wenqiang Jiang (Chemical Engineering Journal, 2023)

Research on the risk evaluation of urban wastewater treatment projects based on an improved fuzzy cognitive map - Hongyu Chen; Jingyi Wang; Zongbao Feng; Yang Liu; Wen Xu; Yawei Qin (Sustainable Cities and Society, 2023)

Numerical validation of analytical solutions for tunnels and their applicability evaluation index - Yawei Duan; Jingqi Huang; Mi Zhao; Xu Zhao; Huifang Li; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2023)

Quantitative generation of ROS and their effective photocatalytic antibacterial activity of high-intensity universal P25 network films: The role of ROS - Jin Xu; Chengzhuo Yu; Silong Wang; Li Xiong; Fanglan Geng; Jitao Lv; Lixia Zhao; Yawei Wang (Journal of Environmental Chemical Engineering, 2023)

Analytical solutions for stresses and displacements of tunnels under static and seismic loading - Yawei Duan; Jingqi Huang; Xu Zhao; Mi Zhao; Huifang Li; Xiuli Du (Computers and Geotechnics, 2023)

Coating TiO2 with MIL-101(Fe) to decarboxylate D-Glu and D-MeAsp of microcystin-LR from HA-rich water: Diminishing the inhibitory effect of humic acids - Yarui Wang; Chengzhuo Yu; Sen Wang; Jin Xu; Fanglan Geng; Silong Wang; Jitao Lv; Lixia Zhao; Yawei Wang (Chemical Engineering Journal, 2023)

Impact of pyraclostrobin on the growth of Fusarium pseudograminearum and its control efficacy against wheat crown rot in Henan Province, China - Ying Hou; Yawei Chen; Lili Wang; Yiheng Zheng; Shengming Liu; Jianqiang Xu (Journal of Plant Pathology, 2023)

An extensive assessment of seasonal rainfall on intracellular and extracellular antibiotic resistance genes in Urban River systems - Wenchao Yu; Ye Xu; YaWei Wang; Qianwen Sui; Yuan Xin; Hui Wang; Junya Zhang; Hui Zhong; Yuansong Wei (Journal of Hazardous Materials, 2023)

Nrf2 protects against renal fibrosis induced by chronic cadmium exposure in mice - Chengjie Chen; Zhengsheng Zhou; Siqi Yu; Yawei Ma; Gang Wang; Xue Han; Congcong Jiao; Junjun Luan; Zhiyuan Liu; Yuanyuan Xu; Huihui Wang; Qiang Zhang; et al. (Food and Chemical Toxicology, 2023)

Experimental research on the flame resistance characteristics of wire mesh for syngas explosion - Xingyan Cao; Zhi Wang; Zhirong Wang; Yawei Lu; Shaochen Sun; Jianjun Xu (Process Safety and Environmental Protection, 2023)

Reaction mechanism of NO and SO2 Co-removal by calcium hydroxide - Angran Zhao; Yongqiang Han; Zhipeng Wang; Pengfei Li; Yawei Xu; Ruiming Yang; Huiling Tong (Journal of Environmental Chemical Engineering, 2023)

Reinforcing supramolecular hyaluronan hydrogels via kinetically interlocking multiple-units strategy - Ruofan Chen; Yujie Li; Yu Jin; Yawei Sun; Zhiyong Zhao; Yun Xu; Jiang-Fei Xu; Yuanchen Dong; Dongsheng Liu (Carbohydrate Polymers, 2023)

Environmental characteristics and unified failure mode classification system for mining landslides in the karst mountainous areas of southwestern China - Zuliang Zhong; Yawei Xu; Nanyun Wang; Xinrong Liu; Guofu Gao (Carbonates and Evaporites, 2023)

Experimental and theoretical study on the suppression effect of water mist containing dimethyl methylphosphonate (DMMP) on hydrogen jet flame - Zhirong Wang; Hui Xu; Yawei Lu; Zhenhua Tang; Rujia Fan (Fuel, 2023)

Radial and seasonal variation of sap flow and its response to meteorological factors in sandy Pinus sylvestris var. mongolica plantations in the Three North Shelterbelt of China - Yuqiang Tong; Jing Liu; Xu Han; Tong Zhang; Yinghao Dong; Mengge Wu; Shengjin Qin; Yawei Wei; Zhenju Chen; Yongbin Zhou (Agricultural and Forest Meteorology, 2023)

Twin peaks of in-hospital mortality among patients with STEMI across five phases of COVID-19 outbreak in China: a nation-wide study - Jianping Li; Nan Zhang; Ziyi Zhou; Xiao Huang; Weiyi Fang; Hongbing Yan; Jiyan Chen; Weimin Wang; Dingcheng Xiang; Xi Su; Bo Yu; Yan Wang; et al. (Science China Life Sciences, 2022)

Multi-Tunnel Triboelectric Nanogenerator for Scavenging Mechanical Energy in Marine Floating Bodies - Ziyi Zhang; Zhiyuan Hu; Yan Wang; Yawei Wang; Qiqi Zhang; Dehua Liu; Hao Wang; Minyi Xu (Journal of Marine Science and Engineering, 2022)
The ocean has an abundant reserve of wave energy, which is considered to be a clean, widely distributed and inexhaustible resource. Triboelectric nanogenerators (TENGs) have been regarded as a reliable technology for harvesting wave energy due to its robustness and efficiency in scavenging random mechanical energy. In this study, a wave energy harvesting multi-tunnel TENG (MT-TENG) has been proposed, which could be integrated easily with ocean buoys. The MT-TENG consists of polytetrafluoroethylene (PTFE) balls and a multi-tunnel frame, which could convert wave energy into electrical energy. The multi-tunnel design also avoids possible mutual obstruction of the PFTE balls during the movement. Compared with the flat type structure, the multi-tunnel structure could enhance output performance obviously. With an agitation frequency of 2 Hz and vibration amplitude of 130 mm, the MT-TENG has a peak power density of 8.3 W/m3, which is five times that of the flat type structure TENG. By integrating with a life buoy and floating pipe line, the MT-TENG could harvest wave energy to light LEDs continuously, which could provide a new solution for maritime rescue and night offshore oil delivery warning.

Fluctuations in the heart rate of abalone in response to low salinity stress - Grace Afumwaa Boamah; Feng Yu; Yawei Shen; Weiwei You; Changan Xu; Xuan Luo; Caihuan Ke (Aquaculture International, 2022)

Changing incidence and projections of thyroid cancer in mainland China, 1983–2032: evidence from Cancer Incidence in Five Continents - Mandi Li; Jiao Pei; Minghan Xu; Ting Shu; Chengjie Qin; Meijing Hu; Yawei Zhang; Min Jiang; Cairong Zhu (Cancer Causes & Control, 2021)

Research on the mechanical properties and electrical conductivity of cement mortar based on recycled nano-iron boride - Wei He; Zhinan Jiao; Yawei Wang; Jihang Xu; Qingxin Zhao (Waste Disposal & Sustainable Energy, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Nitrification inhibitor DMPP offsets the increase in N2O emission induced by soil salinity - Yawei Li; Junzeng Xu; Xiaoyin Liu; Zhiming Qi; Haiyu Wang; Youjia Li; Linxian Liao (Biology and Fertility of Soils, 2020)

Antimicrobial Peptide JH-3 Effectively Kills Salmonella enterica Serovar Typhimurium Strain CVCC541 and Reduces Its Pathogenicity in Mice - Lei Wang; Xueqin Zhao; Xiaojing Xia; Chunling Zhu; Wanhai Qin; Yanzhao Xu; Bolin Hang; Yawei Sun; Shijun Chen; Huihui Zhang; Jinqing Jiang; Jianhe Hu; et al. (Probiotics and Antimicrobial Proteins, 2019)

Ammonia volatilization and nitrogen leaching following top-dressing of urea from water-saving irrigated rice field: impact of two-split surge irrigation - Junzeng Xu; Boyi Liu; Haiyu Wang; Wenhao Liu; Yawei Li; Yubin Dai; Tao Lu (Paddy and Water Environment, 2019)

Influence of Atmospheric Particulate Matter on Ozone in Nanjing, China: Observational Study and Mechanistic Analysis - Yawei Qu; Tijian Wang; Yanfeng Cai; Shekou Wang; Pulong Chen; Shu Li; Mengmeng Li; Cheng Yuan; Jing Wang; Shaocai Xu (Advances in Atmospheric Sciences, 2018)

A novel 76-mer peptide mimic with the synergism of superoxide dismutase and glutathione peroxidase - Yawei Xu; Yan Zhou; Rui Yin; Cheng Wang; Haijiao Chu; Junling Wang (In Vitro Cellular & Developmental Biology - Animal, 2018)

Transcriptome profiles reveal cold acclimation and freezing tolerance of susceptible and tolerant hulless barley genotypes - Hongjun Yuan; Xingquan Zeng; Zhihao Ling; Zexiu Wei; Yulin Wang; Zhenhua Zhuang; Qijun Xu; Yawei Tang; Nyima Tashi (Acta Physiologiae Plantarum, 2017)

The cyclin dependent kinase subunit Cks1 is required for infection‐associated development of the rice blast fungus Magnaporthe oryzae - Xiaofeng Yue; Yawei Que; Shuzhen Deng; Lin Xu; Miriam Oses‐Ruiz; Nicholas J. Talbot; Youliang Peng; Zhengyi Wang (Environmental Microbiology, 2017)
Summary Cell cycle regulation is pivotal for proper cell division and cellular differentiation in eukaryotic cells. The central regulators that govern eukaryotic cell cycle progression are cyclin‐dependent kinases (CDKs) and their partners. Here, we report that Magnaporthe oryzae CKS1 encodes a cyclin‐dependent kinase subunit, which plays a significant role in regulation of plant infection. We demonstrate that CKS1 is a functional homolog of CKS1 / SUC1 and can physically interact with the CDK protein Cdc28, and Som1, a downstream regulator of the cyclic AMP‐dependent Protein Kinase A pathway. CKS1 deletion mutants are severely impaired in hyphal growth, sexual reproduction, melanin pigmentation and conidiogenesis. Cks1 mutants are able to form appressoria from hyphal tips, but these are unable to re‐polarize, and rice infection is impaired. CKS1 also affects chitin and glucan synthase activity during cell wall differentiation and fungal hydrophobin function. CKS1 , therefore, encodes a conserved CDK‐binding partner, essential for appressorium‐mediated plant infection by the rice blast fungus.

Adiponectin Suppresses T Helper 17 Cell Differentiation and Limits Autoimmune CNS Inflammation via the SIRT1/PPARγ/RORγt Pathway - Kai Zhang; Yawei Guo; Zhenzhen Ge; Zhihui Zhang; Yurong Da; Wen Li; Zimu Zhang; Zhenyi Xue; Yan Li; Yinghui Ren; Long Jia; Koon-Ho Chan; et al. (Molecular Neurobiology, 2017)

Erratum to: Transcriptomics analysis of hulless barley during grain development with a focus on starch biosynthesis - Yawei Tang; Xingquan Zeng; Yulin Wang; Lijun Bai; Qijun Xu; Zexiu Wei; Hongjun Yuan; Tashi Nyima (Functional & Integrative Genomics, 2017)

Transcriptomics analysis of hulless barley during grain development with a focus on starch biosynthesis - Yawei Tang; Xingquan Zeng; Yulin Wang; Lijun Bai; Qijun Xu; Zexiu Wei; Hongjun Yuan; Tashi Nyima (Functional & Integrative Genomics, 2017)

Metals compositions of indoor PM2.5, health risk assessment, and birth outcomes in Lanzhou, China - Yaqun Zhang; Suzhen Cao; Xiaoying Xu; Jie Qiu; Mingxia Chen; Dennis Wang; Donghong Guan; Chengyuan Wang; Xiao Wang; Bowen Dong; Huang Huang; Nan Zhao; et al. (Environmental Monitoring and Assessment, 2016)

Air Quality in Lanzhou, a Major Industrial City in China: Characteristics of Air Pollution and Review of Existing Evidence from Air Pollution and Health Studies - Yaqun Zhang; Min Li; Mercedes A. Bravo; Lan Jin; Amruta Nori-Sarma; Yanwen Xu; Donghong Guan; Chengyuan Wang; Mingxia Chen; Xiao Wang; Wei Tao; Weitao Qiu; et al. (Water, Air, & Soil Pollution, 2014)